Internet connectivity disruption in Iran (Iran) - Voidly (2026)
CRITICAL severity disruption detected in Iran. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: IR-2026-0209
Keywords: internet disruption; IR; disruption; critical